Information Management Technology - Burton, Paul F. author. aut Link
IX, 216 p.
Keywords: Once again the wide-ranging and rapid developments in microcomputer technology of the last few years have meant that a detailed revision of The librarian's guide to microcomputers for information management was required, if it was to fulfil its objectives of providing a single source of information on the process of automating with a microcomputer. For this new edition, we have taken into account not only the developments in hardware, but also the growing sophistication and power of software, and the growing sophistication of library and information service managers. The latter are more and more familiar with the use, or at least the principles, of microcomputers, and it no longer seems necessary to spell out certain details. We have, where relevant, indicated sources of more detailed information, particularly of practical applications, and so we hope that the changes we have made will ensure that this book remains of value to practitioner and student alike. ACKNOWLEDGEMENTS We remain, as always, grateful to those who have written or spoken about their experiences with microcomputers and have described applications. We would also like to thank the referees who commented of the book, and provided useful suggestions and on a first draft amendments. Mandy and Lindesay once again patiently accepted our absence during the writing of this edition.